Pengaruh Penyuluhan Tentang Stunting Dan Cara Pengukurannya Terhadap Pengetahuan Kader Di Desa Malangjiwan Kecamatan Colomadu Kabupaten Karanganyar - Kisnawaty, Sudrajah Warajati; Mustikaningrum, Fitriana; Dayanti, Abela Rhestu; Afifah, Afifah; Styaningsih, Aulia; Luthfilhadi, Farisin Hanif (Bengawan : Jurnal Pengabdian Masyarakat, 2025)
Stunting is one of the main public health issues in Indonesia, affecting children's physical growth, cognitive development, and future productivity. One of the key strategies in preventing stunting is improving the competencies of posyandu (integrated health post) cadres in monitoring the growth of toddlers through proper anthropometric measurement training. This community service activity was conducted in Malangjiwan Village, Colomadu Sub-district, Karanganyar Regency, involving 35 posyandu cadres, with 21 cadres participating in the evaluation. The methods used included education on stunting and training in anthropometric measurements using a baby length board, microtoise/stadiometer, KMS (Child Growth Chart), and anthropometric tables. Evaluation was carried out using pre-test and post-test questionnaires assessing the cadres' knowledge. The results showed a significant increase in knowledge, with the average pre-test score rising from 59.18% to 72.79% in the post-test. The Wilcoxon Signed Rank Test showed a p-value of 0.000 (p < 0.05), indicating a significant difference before and after the training. These findings confirm that direct and structured training for cadres is effective in increasing knowledge about stunting and anthropometric measurement skills, which is expected to enhance the quality of toddler growth monitoring at posyandu and strengthen their role in stunting prevention at the village level.